Offspring Exercise Modulates Beige Adipocyte Numbers by Differential Regulation of H3K9 Methyltransferase G9a and Demethylase KDM4C in Mice Fed a Maternal High Fat Diet (P21-067-19). (13th June 2019) - Larson, Kate; Bundy, Amy; Alvine, Travis; Lance, Elizabeth Black; Roemmich, James
Abstract: Objectives: We have shown that a maternal low protein and postnatal high fat (HF) diet increases offspring obesity and type 2 diabetes mellitus (T2DM) risk by epigenetically reducing beige adipocyte (BA) numbers via increased protein expression of G9a (Histone3 Lysine9 dimethyl transferase), an inhibitor of the BA marker FGF21. It is not yet known whether offspring exercise reverses the offspring obesity and T2DM risk caused by the maternal HF diet. Methods: Two month old female C57Bl/6 J mice (F0) were fed a normal fat (NF) 16% diet or a 45% HF diet for 3 months prior to breeding, and subsequent gestation and lactation. Male offspring (F1) were fed the same NF and HF diets and further divided into either cage active (CA) or voluntary wheel running (Ex) groups for an additional 3 months yielding eight groups: NF (maternal treatment condition)-Ex-NF (post weaning treatment conditions), NF-Ex-HF, NF-CA-NF, NF-CA-HF, HF-Ex-NF, HF-Ex-HF, HF-CA-NF, and HF-CA-HF. Subcutaneous adipose tissue samples were collected for protein and mRNA analysis of FGF21, G9a, E4BP4 (G9a coactivator), and H3K9 methylation regulators that are induced by exercise including Activating Transcription Factor 4 (ATF4) and H3K9 demethylases (KDM4C). Results: Postnatal HF diet decreased FGF21 positive BA numbers regardless of the maternal diet. A postnatal HF diet plus limited postnatal activity (CA) increased G9a and E4BP4 expression to suppress FGF21, while a postnatal HF diet plus exercise condition increased KDM4C expression. Although BA were detectable, the morphology of BA under CA conditions were compromised or scarred. Conclusions: These findings suggest that a postnatal HF diet has a greater impact on offspring adiposity and BA number than a maternal HF diet. These data also suggest that offspring exercise induces KDM4C to counter the increase in G9a triggered by a postnatal HF diet. Whether KDM4C induces reduction in H3K9-me2 to regulate adipose tissue FGF21 needs investigation. Futures studies should determine whether H3K9 epigenetic modifications in BA have any functional differences that contribute to the observed phenotypic abnormalities. Funding Sources: USDA Agricultural Research Service Project #3062-51000-052-00D.